Collisions And Clarifications Of The Criminal Legislation Of The Republic Of Kazakhstan - Akimzhanov, Talgat; Baybek, Zhanar (Opción, 2019)
The article reveals the content of the purposes on criminal penalty enshrined in the Criminal legislation of the Republic of Kazakhstan via comparative qualitative research methods. As a result, the legislative reflection of private prevention is traced concerning the legislator to responsibility for the recurrence of crimes: with the strengthening of the recurrence, it is amplified responsibility as well. In conclusion, such an important question of criminal law, as the purposes of punishment, needs further judgment and improvement, as it has as theoretical and practical value as well.